2000
DOI: 10.1080/10942910009524644
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristics of fermented sour fish cake (Nham‐Pla)

Abstract: Nham-Pla (fermented sour fish cakes) were made from four kinds of fish, namely, striped catfish and nile tilapia from the fresh water fish and threadfin bream and barracuda from the marine fish. Sensory evaluation tests showed that Nham-Pla made from the fresh water fish have a higher acceptability score; and score differences between catfish and nile tilapia are insignificant. However, score differences between threadfin bream and barracuda are noticeably large. Chemical analysis and Microbiological analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…The bacterial counts increased rapidly by day 2, reaching levels of 8.98–9.02 log CFU/g, and remained stable thereafter. These results align with those of Sangjindavong et al [ 37 ], who observed stable TVC and LAB levels in fermented barracuda during days 2–7 of fermentation.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The bacterial counts increased rapidly by day 2, reaching levels of 8.98–9.02 log CFU/g, and remained stable thereafter. These results align with those of Sangjindavong et al [ 37 ], who observed stable TVC and LAB levels in fermented barracuda during days 2–7 of fermentation.…”
Section: Resultssupporting
confidence: 92%
“…LAB play key roles in fish sausage fermentation [ 3 , 37 , 38 ]. Several LAB species produce amylase, which converts starch into glucose [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation